Comparison of the efficacy of pulsed radiofrequency in treating acute herpetic neuralgia and postherpetic neuralgia in the thoracic segment - Wang, Huan; Zhang, Dandan; Wang, Shiyu; Wang, Hui; Nie, Huiyong (Frontiers in Neurology, 2024)
Objectives: This study aimed to compare the efficacy of pulsed radiofrequency(PRF) to dorsal root ganglia(DRG) in treating acute herpetic neuralgia(AHN) and postherpetic neuralgia(PHN) in thoracic segment. Methods: A total of 243 patients with thoracic herpes zoster related pain(AHN or PHN) from January 2020 to September 2022 were retrospectively analyzed. They were divided into two groups according to the timing of PRF after herpes zoster onset: an acute herpetic neuralgia group(within 90 days) and a postherpetic neuralgia group(more than 90 days). All patients were treated with PRF at the thoracic DRG. The Visual Analogue Scale(VAS), Athens Insomnia Scale (AIS), Generalized Anxiety Disorder 7 items (GAD-7) and Patient Health Questionnaire 9 items (PHQ-9) before and 1 week, 1 month, 3 months, 6 months and 12 months after surgery were analyzed and compared between the two groups. Results: Postoperative scores of VAS, AIS, GAD-7 and PHQ-9 in both groups were significantly lower than those before surgery(P<0.001).The VAS, AIS, GAD-7 and PHQ-9 scores in AHN group from 1 month to 12 months after surgery were significantly lower than those in PHN group(P<0.001). The VAS, AIS, GAD-7 and PHQ-9 scores of the AHN group showed a gradual improve from 1 week to 12 months after surgery. While the VAS, AIS, GAD-7 and PHQ-9 scores of the PHN group began to worse and worse slowly from 1 week to 12 months after surgery. With the extension of postoperative follow-up time, the difference in scores between the two groups also increased gradually. Conclusion: PRF to DRG is an effective treatment for patients with AHN and PHN who do not respond well to conventional treatment. Especially for patients with AHN, PRF to DRG is more conducive to early pain control, improve sleep and psychological status, and even prevent the occurrence of PHN.